2021
DOI: 10.1111/ppa.13382
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and evolutionary dynamics of tomato black ring virus population

Abstract: Tomato black ring virus (TBRV) is an important pathogen infecting a wide range of plant species worldwide. Phylogenetic studies of TBRV have already been conducted, although limited by the use of short genomic regions or a reduced amount of isolates.In the present study, we carried out an exhaustive phylogenetic and population genetic analysis based on the coat protein gene (CP) sequence of 57 TBRV isolates originating from different host plants and European geographic regions (47 isolates from Poland, 8 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…More evidence for recombination was found within RNA1 than in RNA2 and multiple events (seven from the eight isolates of TBRV/BRSV) were more common than single events. This mirrors the findings of Budzyńska et al (2021) who found that intraspecies recombination was common in TBRV and suggested it is likely to be a major mechanism shaping TBRV populations. In contrast with the two earlier studies, we also found interspecies recombination.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…More evidence for recombination was found within RNA1 than in RNA2 and multiple events (seven from the eight isolates of TBRV/BRSV) were more common than single events. This mirrors the findings of Budzyńska et al (2021) who found that intraspecies recombination was common in TBRV and suggested it is likely to be a major mechanism shaping TBRV populations. In contrast with the two earlier studies, we also found interspecies recombination.…”
Section: Discussionsupporting
confidence: 89%
“…As previously noted for TBRV by Zarzyńska‐Nowak et al (2020) and Budzyńska et al (2021) and in our analysis using RDP4, considerable intraspecies recombination was identified within the genomes of both TBRV and BRSV. For TBRV, there was intraspecies recombination within 6 of 15 isolates for RNA1 and 5 of 15 isolates for RNA2.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Because recombination occurs commonly in complete TBRV and BRSV genomic sequences, two non-recombinant portions of its RNA2 CP gene (P1 nts 1 to 477, and P2 nts 478 to 1533) were used in recent phylogenetic comparisons involving these two viruses (Budzyńska et al 2021;Fowkes et al 2022). The P1 and P2 nt sequence portions of isolate IF were compared with those of the same 15 TBRV or BRSV isolates included previously in the comparison of Fowkes et al (2022).…”
mentioning
confidence: 99%